Human-Data Interaction Design Guidelines for Visualization Systems - Victorelli, Eliane Zambon; dos Reis, Julio Cesar (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The design of interactive visualization systems is challenging due to several aspects involving data interpretation and manipulation mechanisms. Designers need adequate support in the conception of these tools for facilitating the interaction of users with data. In this article, we propose a set of design guidelines on Human-Data Interaction (HDI) with focus on information visualization (IV). Our recommendations were elaborated based on analysis and summary of knowledge from literature, combined with our own design experience with this kind of systems. This study shows to which extent the organized guidelines were understood, used and discussed by Computer Science students in the construction and evaluation of software prototypes for data-driven decision making. Participants were able to understand the guidelines and applied them with success for evaluation of HDI in IV systems.